Numerical simulation of natural convection and heat transfer in a molten pool with embedded cooling tubes - Zhang, Li; Guo, Pengya; Yuan, Yidan; Liang, Yangyang; Guo, Yong; Li, Wei; Guo, Qiang; Ma, Weimin (Frontiers in Energy Research, 2022)
This study described the natural circulation and heat transfer of a molten pool in a specifically designed core catcher conceived for a pressurized water reactor. In addition to external cooling, the core catcher features internal cooling tubes embedded in the molten pool. To investigate the coolability in such a configuration, first, a full-scale core catcher simulation is conducted to give a preliminary study under a real SA situation. Results illustrated that cooling efficiency can be remarkably enhanced due to the inner tubes. Then a test facility of the 2D slice with the geometrical scaled factor of 1:4 has been developed, and molten salt (NaNO3–KNO3) experiments will be implemented in the near future. This study also performed a pre-test simulation using molten NaNO3–KNO3 as a stimulant to study the heat transfer and flow characteristics of the salt pool. The melt convection in the test section was represented by a two-dimensional mesh with a WMLES turbulence model using the FLUENT code. The simulation captured the heat transfer enhancement by the cooling tubes as expected, and the results would help decide the proper test matrix and improvement of instrumentation required to obtain the necessary data for code validation.